舌下腺に発生し診断に苦慮したオンコサイトーマの１例 - 竹村 彩夏; 福嶋 大将; 森下 廣太; 鳴瀬 智史; 片瀬 直樹; 山田 朋弘 (日本口腔外科学会雑誌, 2025)
We report a case of oncocytoma arising in the sublingual gland. The patient was a 53-year-old woman referred to our department because of a swelling in the left oral floor. Magnetic resonance imaging revealed a mass with clear borders measuring approximately 25 × 20 mm in the left sublingual space, showing heterogeneous enhancement with contrast. The initial pathological diagnosis from a tissue biopsy was mucoepidermoid carcinoma. The patient underwent a tumor resection under general anesthesia. Pathological examinations showed that tumor cells consisted of proliferation of eosinophilic cells with granular cytoplasm, and immunohistochemistry revealed that the tumor cells showed a diffuse positive reaction for mitochondria. Based on these findings, the lesion was finally diagnosed as oncocytoma. No sign of recurrence has been observed one year and two months after surgery.